Stakeholder perceptions of forest disturbance drivers and management responses are aligned in Central Europe - Michaela Perunová; Roman Modlinger; Vilém Jarský; Tomáš Hlásny (Ambio, 2026)
Forest disturbances are increasingly understood as social-ecological phenomena involving diverse actors. Here, we focused on one of the Europe’s largest recent disturbances—the drought-triggered bark beetle outbreak in Central Europe (2017–2022). Based on a survey of 165 respondents, we examined perceived disturbance drivers, response actions, and the alignment between them as an indicator of a value-action gap that is often present in social-ecological and governance systems. Climatic and forest structure-related factors were identified as the dominant drivers, aligning with current scientific understanding, whereas socio-economic and management constraints were perceived as less influential. Reported responses reflected awareness of climate-change risks and involved workforce training, adaptive change in species composition, and water-retention measures. Cause–action alignment was observed in nearly half of respondents, particularly among managers and legal entities. We found a relatively sound understanding of disturbance causes and corresponding responses, likely shaped by recent experience with an unprecedented disturbance impact.

Tree Regeneration After Unprecedented Forest Disturbances in Central Europe Is Robust but Maladapted to Future Climate Change - Mária Potterf; Christian Schattenberg; Kirsten Krüger; Kilian Hochholzer; Werner Rammer; Marc Grünig; Kristin H. Braziunas; Christina Dollinger; Aikio Erhardt; Jean‐Claude Gégout; Lisa Geres; Sina Greiner; et al. (Global Change Biology, 2026)
Central Europe has been a hotspot of forest disturbance during 2018–2020, with large pulses of tree mortality from drought and bark beetles. Post‐disturbance recovery is crucial for forest resilience and the continued provision of ecosystem services. We surveyed 849 plots in disturbance hotspots across 10 Central European countries to assess the state of early (3–5 years) post‐disturbance tree regeneration. Our specific objectives were to quantify post‐disturbance tree recovery, identify key drivers, and assess future trajectories using model‐based analyses. We found robust tree recovery throughout Central Europe, with median stem densities of 4750 n ha −1 . Only 7% of plots had no regeneration. Regeneration density increased with precipitation, particularly at warm sites, and decreased with disturbance size. The most frequently regenerating tree species was Picea abies (present on 48% of plots), a species that is poorly adapted to future heat and drought. Overall, we found that 75% of the currently established trees are projected to be outside of their climatic niche by the end of the century under moderate climate change (RCP4.5). We conclude that while Central European forests recover well from recent disturbances, they lack sufficient post‐disturbance reorganization to enable sufficient adaptation to future climate.

Response of mature Norway spruce to experimental thermal and drought stress in relation to Ips typographus attack: Crown temperatures and sap flow - Aleksandr Karpov; Nana Pirtskhalava-Karpova; Vivek Vikram Singh; Aleksei Trubin; Nataliya Korolyova; Roman Modlinger; Rastislav Jakuš (Forest Ecology and Management, 2026)

Perspectives: State of national forest damage survey programmes in Europe and ways toward improved harmonization and data sharing - Tomáš Hlásny; Michaela Perunová; Roman Modlinger; Max Blake; Gediminas Brazaitis; György Csóka; Maarten de Groot; Mihai-Leonard Duduman; Massimo Faccoli; Margarita Georgieva; Georgi Georgiev; Wojciech Grodzki; et al. (Forest Ecology and Management, 2025)

Divergent Trends in Insect Disturbance Across Europe's Temperate and Boreal Forests - Tomáš Hlásny; Roman Modlinger; Jostein Gohli; Rupert Seidl; Paal Krokene; Iris Bernardinelli; Simon Blaser; Gediminas Brazaitis; Gailenė Brazaitytė; Eckehard G. Brockerhoff; György Csóka; Laura Dobor; et al. (Global Change Biology, 2025)
Ongoing shifts in climate and land use have altered interactions between trees and insect herbivores, changing biotic disturbance regimes. However, as these changes are complex and vary across host species, insect taxa, and feeding guilds, they remain poorly understood. We compiled annual records of forest insect disturbance from 15 countries in temperate and boreal Europe, spanning the period from 2000 to 2022. The dataset comprises 1361 time series characterizing the dynamics of 50 herbivorous insects. We used this dataset to test whether insect disturbance has systematically changed during the 23‐year period across host trees and feeding guilds, whether it varies along latitudinal and climatic gradients, and whether synchrony exists among species in the same guild or among species sharing the same host. Since 2000, borer disturbance was predominantly concentrated on gymnosperms, while defoliators impacted gymnosperms and angiosperms more evenly. While 85.8% of gymnosperm disturbance was inflicted by a single species, Ips typographus , the majority of disturbances to angiosperms were caused by six different species. Borer impact on gymnosperms has increased in the 21st century, while defoliator impact has decreased across both clades. In contrast to diverging temporal trends, disturbance was consistently greater in warmer and drier conditions across feeding guilds and host types. We identified significant synchrony in insect disturbance within host types and feeding guilds but not between these groups, suggesting shared drivers within guilds and host types. Increasing insect disturbance to gymnosperms may catalyze adaptive transformations in Europe's forests, promoting a shift from historical conifer‐dominated management to broadleaved trees, which are less affected by insect herbivores. Our findings reveal a diversity of trends in insect herbivory, underscoring the need to strengthen monitoring and research in order to better understand underlying mechanisms and identify emerging threats that may not be apparent in currently available data.

Spectral signatures discrimination of Norway spruce trees under experimentally induced drought and acute thermal stress using hyperspectral imaging - Matúš Pivovar; Roope Näsi; Eija Honkavaara; Miroslav Blaženec; Jaroslav Škvarenina; Roman Modlinger; Jaroslav Rožnovský; Rastislav Jakuš (Forest Ecology and Management, 2025)

Detection of green attack and bark beetle susceptibility in Norway Spruce: Utilizing PlanetScope Multispectral Imagery for Tri-Stage spectral separability analysis - Aleksei Trubin; Giorgi Kozhoridze; Khodabakhsh Zabihi; Roman Modlinger; Vivek Vikram Singh; Peter Surový; Rastislav Jakuš (Forest Ecology and Management, 2024)

Gene expression plasticity facilitates different host feeding in Ips sexdentatus (Coleoptera: Curculionidae: Scolytinae) - Gothandapani Sellamuthu; Aisha Naseer; Jaromír Hradecký; Amrita Chakraborty; Jiří Synek; Roman Modlinger; Amit Roy (Insect Biochemistry and Molecular Biology, 2024)

Multi-decade patterns of gypsy moth fluctuations in the Carpathian Mountains and options for outbreak forecasting - Tomáš Hlásny; Jiří Trombik; Jaroslav Holuša; Karolina Lukášová; Marian Grendár; Marek Turčáni; Milan Zúbrik; Mara Tabaković-Tošić; Anikó Hirka; Igor Buksha; Roman Modlinger; Magdalena Kacprzyk; et al. (Journal of Pest Science, 2016)